GC–MS analysis for compound identification in leaf extract of Lumnitzera racemosa and evaluation of its in vitro anticancer effect against MCF7 and HeLa cell lines - G. Eswaraiah; K. Abraham Peele; S. Krupanidhi; M. Indira; R. Bharath Kumar; T.C. Venkateswarulu (Journal of King Saud University: Science, 2020)
The aim of present study is to analyze and separate bioactive constitutes of methanol leaf extract from Lumnitzera racemosa by Gas chromatography–Mass spectroscopy (GC–MS) and further to test for in vitro anticancer activity on MCF 7 and HeLa cancer cells using MTT assay. GC–MS analysis of L. racemosa leaf extract showed the presence of different bioactive compounds mainly: furfurals and fatty acids. The bioactive compounds present in L. racemosa revealed significant cytotoxic activity against MCF 7 with IC50 value, 46.098 µg/mL and HeLa cells with IC50 value of 59.497 µg/mL. The leaf extracts of L. racemosa has high anticancer activity on MCF 7 cells in comparison with HeLa cell lines. Keywords: Lumnitzera racemosa, Bioactive compounds, Mangrove species, Methanol, GC–MS